Tumor Cellular and Microenvironmental Cues Controlling Invadopodia Formation - Masi, Ilenia; Caprara, Valentina; Bagnato, Anna; Rosanò, Laura (Frontiers in Cell and Developmental Biology, 2020)
During the metastatic progression, invading cells might achieve degradation and subsequent invasion into the extracellular matrix (ECM) and the underlying vasculature using invadopodia, F-actin-based and force-supporting protrusive membrane structures, operating focalized proteolysis. Their formation is a dynamic process requiring the combined and synergistic activity of ECM-modifying proteins with cellular receptors, and the interplay with factors from the tumor microenvironment (TME). Significant advances have been made in understanding how invadopodia are assembled and how they progress in degradative protrusions, as well as their disassembly, and the cooperation between cellular signals and ECM conditions governing invadopodia formation and activity holding promise to translation into the identification of molecular targets for therapeutic interventions. These findings have revealed the existence of biochemical and mechanical interactions not only between the actin cores of invadopodia and specific intracellular structures, including the cell nucleus, the microtubular network, and vesicular trafficking players, but also with elements of the TME, such as stromal cells, ECM components, mechanical forces, and metabolic conditions. These interactions reflect the complexity and intricate regulation of invadopodia and suggest that many aspects of their formation and function remain to be determined. In this review, we will provide a brief description of invadopodia and tackle the most recent findings on their regulation by cellular signaling as well as by inputs from the TME. The identification and interplay between these inputs will offer a deeper mechanistic understanding of cell invasion during the metastatic process and will help the development of more effective therapeutic strategies.